AppYourself Instant Store (Case Study: SMEs Industry in Aceh Province) - Rizaldi Akbar; Mislina; Yunan Henriyanto; Herry Setiawan (International Journal Software Engineering and Computer Science (IJSECS), 2022)
The purpose of this study is to implement the use of AppYourself to create an Instant Store that can be used in Small and Medium Enterprises (SMEs) Industry in Aceh Province. The Software Development Life Cycle method used is IDI. IDI is a combination of iterative design / iterative method and incremental build model that is used for software development. Testing and measurement based on usability level using the People at the Center of Mobile Application Development (PACMAD) model based on its seven aspects. This research uses Performance Measurement, SUS Questionnaire, NASA-TLX Questionnaire, and RTA Questionnaire in data collection. The data was measured using usability metrics, statistical tests, and calculation formulas from the questionnaire. The results of this study have succeeded in making an application called InstantStore by involving several stages from data collection to testing. The results of the initial test or pre-evaluation and final testing or post-evaluation, it can be concluded that after an evaluation by designing a prototype of improvement recommendations using the rules of The 4 Golden Rules Of User Interface Design, there is a significant increase, based on the results of statistical tests on testing Pre-evaluation shows that there are significant differences between respondents in South Aceh Regency and Banda Aceh City on aspects of efficiency, memorability, satisfaction, and cognitive load. In addition to the aspects of effectiveness, learnability, and errors there is no significant difference between respondents. While the results obtained from statistical tests in the final test (post-evaluation) there are no differences between respondents to the seven aspects of the usability of the PACMAD model.